Clinical efficacy of meridian differentiation acupuncture in the treatment of intractable insomnia based on objective data: a protocol for a multicentre, single-blind, randomised controlled trial - Yun Li; Nan Lin; Bo Li; Ling Gao; Li Dong; Wenming Chu; Xi-Yan Gao; Xueyang Guo; Bo-Yu Zhang (BMJ Open)
Introduction Insomnia, a prevalent sleep disorder, significantly impacts individuals' physical and mental well-being. Despite conventional treatments, some patients experience persistent insomnia. Acupuncture, a safe complementary therapy, has been demonstrated to be effective in treating insomnia. Meridian differentiation can enhance acupuncture efficacy by enabling individualised diagnosis. Previous clinical research has indicated that meridian differentiation acupuncture (MA), based on objective data, can notably enhance sleep quality in patients with intractable insomnia. However, small sample sizes and a lack of objective measures necessitate further investigation. Therefore, we plan to conduct a large-scale, multicentre clinical trial to validate its efficacy.Methods We propose a multicentre, single-blind, randomised, sham acupuncture (SA)-controlled trial involving 489 participants with intractable insomnia. Patients will be randomly assigned to three groups at a 1:1:1 ratio: the MA group, the conventional acupuncture group and the SA group. We will assess Pittsburgh Sleep Quality Index scores, actigraphy, sleep diary, Insomnia Traditional Chinese Medicine Symptom Scale scores, Hamilton Rating Scale for Anxiety scores and meridian imbalance values at baseline, after 2 weeks and 4 weeks of treatment, and at two follow-up periods (8 weeks and 12 weeks postbaseline). The intention-to-treat principle will be applied to analyse the data, observe differences between meridian differentiation acupuncture, CA and SA in improving outcomes related to intractable insomnia.Ethics and dissemination The study protocol has been approved by the Ethics Committee of the Third Affiliated Hospital of Henan University of Traditional Chinese Medicine (2024HL-002) and the ethics committees of other participating institutions. Each participant must provide their written informed consent form before enrolling in this study, and consent can be withdrawn at any stage. On completion of the study, the results will be published in a journal or made available by contacting the corresponding author via email.Trial registration number This study protocol was registered in the Chinese Clinical Trial Registry on 22 April 2024 (ChiCTR2400083323).